Dietary supplementation of Polygonum chinense improves the immunity of Asian seabass, Lates calcarifer (Bloch, 1790) against Vibrio harveyi infection - Abdul Razak Rashidah; Mohamed Shariff; Fatimah Md. Yusoff; Intan Safinar Ismail (Fish and Shellfish Immunology Reports, 2023)
Aquaculture plays a significant role in the overall fish production in Malaysia, contributing a substantial quantity of food-fish amounting to roughly 573,683 tonnes with an estimated economic value of US$860 million in 2022. However, diseases have become a significant limitation for aquaculture production. Therefore, herbal immunostimulant has been considered a natural and practical approach of preventing disease infection in fish. The ability of Polygonum chinense extract (PCE) on haemato-biochemistry parameters, immunomodulatory properties, and disease resistance of Lates calcarifer (Asian seabass) under Vibrio harveyi challenge was evaluated in this study, with a focus on dose-response associations and variability over various exposure durations (0-, 7- and 14-day post-infection). A total of 480 Asian seabass (9.5 ± 0.2 g) were distributed in 12 aquaria and fed four diets supplemented with 0 (control), 2, 5 and 10 g/kg diet for 60 days before being challenged with V. harveyi. Dietary PCE significantly improved (P < 0.05) survival, with the dose of 10 g/kg showing the highest survival rate (90 %) when compared to the control (60 %). Additionally, hematological (red and white blood cell counts, hemoglobulin, packed cell volume, and mean corpuscular volume) and immunological (activities of lysozyme, phagocytic activity and respiratory burst, and serum total immunoglobulin) properties were significantly increased (P < 0.05) in comparison to the control group. In contrast, serum aspartate aminotransferase and alanine aminotransferase levels, as well as glucose level were significantly reduced (P < 0.05) in PCE-fed fish compared to the control group. Conclusively, the current study discovered that supplementing fish feed with P. chinense extract improves fish haemato-biochemical profile, immunocompetence and disease resistance to V. harveyi infection.